Frequency of Self-Acceptance Level and Depression in Association with Death Anxiety Among Patients Suffering from Hepatitis C: Depression in Association with Death Anxiety - Abbas, Salbia; Ashraf, Muhammad Umair; Butt, Rimsha (Pakistan Journal of Health Sciences, 2023)
Considering psychological factors in Hepatitis C patients is essential for providing comprehensive care that addresses both their physical and mental well-being. Objective: To investigate level of self-acceptance and depression in association with death anxiety among patients suffering from HCV. Methods: Present research was a cross-sectional design based on quantitative methodology. Sample entails 92 participants, selected through snowball sampling technique recruited as per the convenience of the researcher. Three constructs were measured by the application of three scales. For the measurement of self-acceptance (LSA), death anxiety (DAQ) and Hamilton depression scale (HRDS), standardized scales with self-administered demographic sheets were used. For the analysis of the data both descriptive and inferential statistics were used. Results: Findings revealed that a positive correlation exists among underlying constructs in the study. Value of correlation depicts that a moderate positive correlation subsists between death anxiety and depression (=230, p<0.01). Moreover, negative relationship exists among LSA, death anxiety (= -420, p<0.01) and depression (= -431, p<0.01). Conclusions: Conclusively, it is stated that level of self-acceptance acts as a mediator in depression and death anxiety. Adequate level of self-acceptance leads to the decline in death anxiety and depression. It can be predicted that patients with high level of self-acceptance are less prone to depression and death anxiety.